Liver Function and Treatment Modalities are Predictors of Survival in Patients with Hepatocellular Carcinoma - Hasan, Irsan; Loho, Imelda Maria; Lesmana, Cosmas Rinaldi; Gani, Rino A. (UI Scholars Hub, 2020)
Introduction. Hepatocellular carcinoma (HCC) is a major health problem in Indonesia because most patients are diagnosed in late stages when curative treatment is no longer possible. The aim of this study is to evaluate one-year survival rate, prognostic factors, and treatment modalities of patients with hepatocellular carcinoma. Methods. A retrospective analysis was done in patients with HCC who were admitted to Cipto Mangunkusumo General Hospital (CMGH) between January 2013 and March 2014. Clinical parameters and treatment modalities were evaluated. Patients outcome at one-year of follow-up were recorded from medical records or patients were contacted by phone call. Survival curve was produced using Kaplan-Meier method and a multivariate analysis was conducted using Cox proportional hazards model. Results. A total of 114 patients were included in this study. Incidence of mortality was 57% and one-year survival rate was 29.4% with median survival as long as 135 days (approximately 4.5 months). According to the BCLC staging system, patients who were diagnosed as early, intermediate, late, and terminal stages were 2 (1.8%), 48 (42.1%), 32 (28.1%), and 32 (28.1%), respectively. Poor liver function (Child-Pugh C class) was diagnosed in 26.3% of patients. Only two patients were diagnosed during surveillance process. Proportion of patients treated with curative/palliative modalities and best supportive care were 34.2% and 65.8%, respectively. In multivariate analysis, Child-Pugh classification and treatment modalities were significant prognostic factors with p-value of <0,001 for both factors. Conclusion. Liver function and treatment modalities are predictors of survival in patients with HCC.